56.8k views
2 votes
X(2y-5z+1)= show work plz

User Ethanolle
by
6.0k points

1 Answer

3 votes

Answer:


2xy-5xz+x

Explanation:

I'm going to assume you wanted to multiply these terms.

To do this, we distribute
x into each term in the parentheses.


2y \cdot x = 2xy\\\\-5x \cdot x = -5xz\\\\1 \cdot x = x

Combining these terms, we get
2xy-5xz+x.

Hope this helped!

User Tenhjo
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.